Performance Study of Drip Irrigation on Andosol Soil with Caisim (Brassica junceaL. ) Cultivation - Dinda Puspa Sari; Sumono Sumono; Nazif Ichwan; Achwil Putra Munir (Jurnal Rekayasa Pangan dan Pertanian, 2014)
Drip irrigation is a more economic method in distributing the water on caisim plant cultivation. This research was aimed to study the drip irrigation performance on Andosol soil with cultivation of caisim plant (Brassica juncea L.). The parameters observed were the characteristic of the soil physics, evapotranspiration, percolation, emission uniformity, use of water and the efficiency of water usage, wet weight and dry weight of caisim plant.Sanded clay textured andosol soil, evapotranspiration on the first growth phase was 0,72 mmday-1, on the middle phase was 1,92 mmday-1 and on the last phase was 0,96 mmday-1. The highest percolation was 2,65 mmday-1 on the middle growth phase on the planted soil and the lowest was 1,11 mmday-1 on the last growth on the non planted soil. The number of emission uniformity was 90,22 %. Efficiency of the highest water usage in the last growth phase on the soil without plant was 35,54 % and efficiency of the lowest in the middle growth phase on the palnted soil was 13,96 %. Efficiency of saving was 100 % on the middle growth phase and on the last. The wet  weight of caisim palnt was 129,5 g while the dry weight of caisim palnt was 7,83 g. Keyword : efficiency, drip irrigation, irrigation performance, Caisim plant, Andosol soil.